Rural sociology in the novel “Sah Al-Nom” by Yahya Haqi - Amouri, Naim; Bharound, Ouali; Massoudiene, Hussein (Journal of Human Sciences, 2022)
Rural sociology emerged in America from the idea centered on social issues with a rural context, which resulted from the exacerbation of the economic and social problems resulting from urbanization. The writers touched on rural issues and presented them with social analyzes. The most famous of them is the writer Yahya Haqi, who lived in a time of confrontations and conflicts; The one who used these confrontations in the clearest possible way, in his famous novel “The Qandil Umm Hashem,” for example, the writer delved into the struggle of the East and the West, between sophistication, civilization, backwardness, and superstitions. and its problems and analyzes its crises through the lens of rural sociology. By using the sociological analysis of the village, we can arrive at the author’s thoughts, his view of society, its issues, and their impact on his books. This study aimed with the descriptive-analytical method to reveal the writer’s vision of the social conditions that were taking place in the Egyptian countryside.